Subject-specific finite element model of knee: experimental validation using composite and bovine specimens. (11th November 2009) - Dressler, Jena L.; Au, Anthony G.; Carey, Jason P.; Amirfazli, A.
This work describes the experimental validation of lower limb finite element models using a composite femur, tibia and bovine tibia. Experimental and predicted equivalent strains and principal strain magnitudes and directions were compared to provide all the necessary information for validation studies. Inaccurate geometry, loading conditions and material properties are frequent errors occurring in validation studies; a sensitivity analysis was done to investigate how the latter two affect the validation. Results were most affected when the directions of the loads were not correctly implemented due to slight misalignment between test apparatus loading axis and the vertical axis in the FE environment.